Development of Mobile Apps NextGen Leadership Program to Improve Managerial Competence and Supervision of Kindergarten Principals - Yafie, Evania; Haqqi, Yudha Alfian; Alif, Adlan; Azizah, Alfi Rohmatul (Jurnal Mutiara Pendidikan, 2025)
The article delves into the development of the NextGen Leadership Program for Mobile Apps. An effective principal manager must know how to encourage teamwork among teachers and other school staff to give them more agency. Encourage the participation of all education staff in a variety of activities that promote school programming and provide opportunity for education personnel to reflect on their profession. However, the conditions in the field found several problems related to the managerial and supervision abilities owned by the school principal. Pay attention to this, a solution is needed to improve the managerial competencies and supervision of the principal. One alternative that can be used is mobile apps based learning tools. The research team behind the NextGen Leadership Program hopes to use the findings to create mobile apps that are both useful and efficient. Data was analyzed using a paired sample t-test, and the methodology employed was a quasi- experiment with a onegroup design that included pre- and post-tests. Results from the NextGen Leadership Program's Mobile App Research Project It can be concluded that there are significant differences in the competencies and supervision of the kindergarten principal before and after using the Mobile Apps NextGen Leadership Program, as the developed results showed a calculation of significance value of 0.000 <0.05.